2021
DOI: 10.7150/thno.54864
|View full text |Cite|
|
Sign up to set email alerts
|

3D-bioprinting ready-to-implant anisotropic menisci recapitulate healthy meniscus phenotype and prevent secondary joint degeneration

Abstract: Objectives: Disruption of anisotropic phenotypes of the meniscus would contribute to OA progression. Exploring phenotype changes of the anisotropic meniscus in joint degeneration would help understand the biologic interaction between the meniscus and OA, and further facilitate the therapeutic strategies of meniscus injury-related joint degeneration. Meanwhile, engineering biomimetic meniscal tissue mimicking the anisotropy of the healthy meniscus remains a challenge. Methods & Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…It is reported that in meniscus, the immune cells and vasculature mainly distributed in the red zone [14]. Meniscus scRNA-seq data were analyzed using the R package Seurat [15], and the cells were clustered at a resolution of 0.6.…”
Section: Identification Of Meniscus Endothelial Cellsmentioning
confidence: 99%
“…It is reported that in meniscus, the immune cells and vasculature mainly distributed in the red zone [14]. Meniscus scRNA-seq data were analyzed using the R package Seurat [15], and the cells were clustered at a resolution of 0.6.…”
Section: Identification Of Meniscus Endothelial Cellsmentioning
confidence: 99%
“…Sun et al constructed engineered cartilage with a hierarchical structure through biotechnology. 39 Its pore structure and growth factors varied gradually with depth, and in vivo experi-…”
Section: Cartilage Regeneration Strategymentioning
confidence: 99%
“…Sun et al constructed engineered cartilage with a hierarchical structure through biotechnology. 39 Its pore structure and growth factors varied gradually with depth, and in vivo experiments showed that the scaffold exhibited a hierarchical structure similar to that of natural cartilage and had excellent integration capacity. Park et al conducted a study on cartilage seed cells, 40 they found that the cell culture system with a three-dimensional structure allowed induced stem cells to differentiate into chondrocytes and maintain their phenotype better than a two-dimensional method of chondrocyte expansion and that a three-dimensional culture system with the addition of TFG-ÎČ3 growth factor showed the greatest number of biomarkers of chondrogenic differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, GDF5 laden constructs were better able to produce hyaline-like neocartilage than constructs without GDF5 MPs, alongside higher GAG and Col II (also indicators of healthy native cartilage, and of chondrocyte phenotype) and displayed better cell spreading and proliferation. Continuing their work, the authors employed 3D bioprinting in the construction of a goat meniscus using a similar approach as above (Sun et al, 2021b). A hydrogel of the same type loaded with goat BMSCs and PLGA MPs containing connective tissue growth factor (CTGF) and (TGFÎČ3) were printed within a PCL scaffold.…”
Section: Cell-based Bioprinting Of Knee Cartilagementioning
confidence: 99%